A familial case of Muckle-Wells syndrome in a Russian population: The first successes of therapy with the interleukin 1 inhibitor canakinumab - S. O. Salugina; E. S. Fedorov; E. Yu. Zakharova; M. D. Evsikova (Современная ревматология)
Muckle-Wells syndrome (MWS) is an autoinflammatory disease belonging to a group of cryopyrin-associated periodic syndromes (CAPS). It is considered to be one of the intermediately severe conditions among CAPSs and to be intermediate between the severest syndrome – Chronic I nfantile Onset Neurologic Cutneous Articular/Neonatal Onset Multisystem Inflammatory Disease (CINCA/NOMID) and the mildest syndrome–Familial Cold Autoinflammatory Syndrome (FCAS). MWS, like all cryopyrinopathies, is caused by a mutation in the NLRP3 (CIAS1) gene; it shows an autosomal inheritance pattern. There are reports on familial MWS cases in the foreign literature; such examples are sporadic in Russia. The given clinical observation clearly demonstrates a genetically verified familial case of MWS in a mother and her daughter in a Russian population and shows how long (occasionally during tens of years or more) the complete complex of the disease may be formed. The results of treatment with the interleukin-1 inhibitor canakinumab in both patients are also given. The high good tolerability and high efficacy of the drug against the clinical manifestations of MWS and acute-phase markers are shown.